Synthesis and thermolysis of copper poly-5-vinyltetrazolate - Zuraev, Alexander V.; Grigoriev, Yuri V.; Grigorieva, Inna M.; Pan’ko, Lyubov I.; Ivashkevich, Ludmila S.; Lyakhov, Alexander S.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2018)
The method for synthesis of copper poly-5-vinyltetrazole salt (Cu-PVT) which based on interaction between the aqueous solutions of sodium poly-5-vinyltetrazolate and Сu(NO3)2 was developed. By using of the solutions of Сu(NO3)2 with a concentration below then 0.3 mol/l, the polymer salt represents as a linear structures with a transverse ionic crosslinks, while the using of more concentrated solutions of Сu(NO3)2 (0.6 mol/l and higher) leads to the formation of globular structures due to the realization in obtained salts intramolecular crosslinks by the metal ion and various kind of coordination interactions. Using differential scanning calorimetry method, it was established that character and energetic parameters of thermal decomposition of Cu-PVT are highly dependent on it preparation conditions. Obtained in the result of thermal decomposition of Cu-PVT product have X-ray amorphous polymeric matrix with copper nanoparticles which show high catalytic activity in phenylacetylene cross-coupling reaction and click-synthesis of difficult to approach 1, 4- and 1, 4, 5-substituted 1H-1, 2, 3-triazoles.
Keywords: poly-5-vinyltetrazole; copper(II) poly-5-vinyltetrazolate; copper nanoparticles; click-synthesis of 1H-1, 2, 3-triazoles; phenylacetylene cross-coupling reactions